Factors Affecting Compliance with The Use of PPE (Personal Protective Equipment) in Nurses the Inpatient Room of Ananda Bekasi Hospital - Ika Amalia; Nuraini Nuraini; Ramadhani Syafitri Nasution (PROMOTOR, 2024)
Occupational health and safety is a crucial aspect in the hospital environment. Even though there are regulations governing the use of Personal Protective Equipment (PPE) by nurses, compliance with its use is still a challenge. This research was conducted at Ananda Bekasi Hospital to understand the factors that influence nurses' compliance in using PPE. Quantitative methods with a cross-sectional approach were used with a sample of 60 nurses from inpatient rooms. Data was obtained through questionnaires, and statistical analysis was carried out using univariate, bivariate and multivariate tests. The results show a significant relationship between work experience, attitudes, knowledge, availability of PPE, supervision, and social support with the use of PPE. The dominant factors influencing the use of PPE are length of service, attitude and social support. The implication is that attention needs to be paid to education, training, better supervision, as well as a supportive culture and attitude to increase compliance with the use of PPE among nurses in hospitals.